Etos Kerja Kristen dan Budaya Mapalus sebagai Perberdayaan Ekonomi Gereja di Minahasa - Feldy Lolangion (Anthropos: Jurnal Antropologi Sosial dan Budaya (Journal of Social and Cultural Anthropology), 2021)
This study aims to understand and provide solutions to poverty problems in the Minahasa area, especially the Protestant church in Minahasa. The problem that appears is the lack of the church in carrying out economic empowerment. On the other hand, the Mapalus culture which is the philosophy of the Minahasa people has begun to be displaced by the times. This makes researchers interested in researching Christian Work Ethics and Mapalus culture as economic empowerment for the church in Minahasa. By using sociological and economic studies, the researcher uses classic theory from Max Weber about The Protestant Ethic and Spirit of Capitalism, and Adam Smith about The Wealth of Nations. To address and examine this problem, this study uses qualitative research, using literature study. Data were collected through literature, references, and articles related to the Protestant work ethic, the Minahasa work ethic, and the spirit of capitalism. Capitalism that is meant by researchers is positive capitalism, where capitalism is running straight with the work ethic of Christians. On the other hand, Minahasa, as a research locus, has a work ethic called Mapalus. Although there are differences between the two work ethics, both can enrich the understanding and morals of church members in Minahasa in carrying out economic empowerment.